TOURISM DESTINATION GOVERNANCE PLAN IN THE REGION CIWIDEY, BANDUNG DISTRICT - Maldini, Muhammad Rizal; R. Wisnu Rahtomo; Daeng Noerjamal (International Journal of Sustainable Competitiveness on Tourism, 2023)
Indonesian development in tourism is an important task of the various stakeholders involved, it is beneficial for all stakeholders because it can grow the community's economy, tourist visits to destinations, valuable tourist experiences, and many others. The management of tourism destinations in an area/destination is very much needed by the stakeholders/stakeholders so that tourism development can be sustainable. One of the areas designated as a Tourism Area is the Ciwidey Area of Bandung Regency which has districts namely Pasir Jambu District, Ciwidey District, and Rancabali District. In this study, the writer took one of the Rancabali Districts, because as many as 35% of the tourism objects in Bandung Regency were located in the Rancabali District and tourists who frequently visited the Ciwidey Region were in the Rancabali Districts. This study uses a Destination Management Organization (DMO) concept pattern which basically can directly involve stakeholders in the management of destinations in a tourism area. In this case, destination governance is not just planning but implementation must be carried out by the stakeholders involved. The concept used regarding stakeholders related to destination governance in this study uses the concept of the level of importance and influence of stakeholders and stakeholder involvement/involvement in destination governance that can improve coordination, communication, and participation between stakeholders. The problems that occur in the Rancabali Region are about tourism objects that have not been well managed, human resources that are utilized for governance are not optimal, there are still stakeholders running each, and coordination and stakeholder involvement are still not optimal. Therefore an organization's management of tourism development must go in one direction and cooperate among stakeholders